Human papillomavirus 68 prevalence and genetic variability based on E6/E7 genes in Sichuan - He, Jiaoyu; Li, Qiufu; Hu, changhua; Peng, Jianying; Ma, Shiyu; Song, Zhilin; Liu, Yiran; Cui, Yanru; Deng, Junhang; Wei, Xia; Ding, Xianping (Virology (New York, N.Y.), 2022)
HPV68 is a common HR-HPV, its persistent infection is closely related with the occurrence of cervical cancer. In this study, 2939 (27.60%, 2939/10650) positive samples were detected, and 174 (5.92%, 174/2939) were HPV68. 150 HPV68 E6-E7 were successful sequenced, 4 non-synonymous mutations were detected in E6, and E7 were 12. N133S non-synonymous mutations of HPV 68 E6 and C67G, T68 A/M of HPV68 E7 are E6, E7 positive selection sites, they all located in the key domains and major motifs of E6/E7 protein, the above amino-acid substitutions changed the protein structure, disturbed the interaction with other protein or cellular factors and make a difference in epitopes affinity, may affect the pathogenicity and adaptability of HPV68 to the environment. The enrichment of HPV68 data is of great significance for understanding the inherent geographical and biological differences of HPV68 in China. •This study is the first to investigate high-risk HPV 68 polymorphism by nuclotide mutation, amino acid substution, protein structure, positive selective and epitopes.•Non-synonymous mutations of HPV 68 located in positive selection sites resulted in differences in protein structure and epitopes affinity, makes HPV-infected cells more difficult/easy to be detected by the immune system, thus change the adaptability of HPV to the environment.•HPV68 data enrichment is of great significance for understanding the inherent geographical and biological differences of HPV68 in china; and targeting potential epitopes for therapeutic vaccines may improve the effective of vaccines design for specific populations.